Aspects of the Natural and the Supernatural in Cicero’s Political Writings - Manuwald, Gesine (Ciceroniana On Line, 2023)
This paper analyses the function of references to natural and supernatural elements in Cicero’s political writings by exploring a selection of case studies. The survey shows that there is usually not an intention to describe details and that these references are instead skilfully adduced to strengthen the respective argument within the discourses and value systems of the period.